Nuclear translocation of nuclear factor kappa B is regulated by G protein signaling pathway in arsenite‐induced apoptosis in HBE cell line. Issue 12 (25th August 2015) - Chen, Chengzhi; Gu, Shiyan; Jiang, Xuejun; Zhang, Zunzhen
ABSTRACT: Arsenite is a certainly apoptosis inducer in various cell types. However, the detailed mechanism underlying how arsenite trigger apoptosis remains elusive. In this study, using human bronchial epithelial cell as a culture system, we demonstrated that arsenite‐induced nuclear translocation of nuclear factor kappa B (NF‐κB) resulted in the release of cytochrome c, the modulation of Fas and FasL, caspase activation, and ultimately leading to cell apoptosis. Importantly, we showed for the first time that the NF‐κB‐mediated apoptosis induced by arsenite was regulated by G protein‐adenylate cyclase (AC)‐cyclic adenosine monophosphate (cAMP)‐protein kinase A (PKA) pathway. Inhibition of this classical G protein signaling pathway by a typical PKA inhibitor, H‐89, caused the inactivation of NF‐κB, the depletion of caspase‐3, 8 and 9 activities, and thus reducing the level of cell apoptosis. Taken together, our results indicate that arsenite is able to trigger cell apoptosis in human bronchial epithelial cells through the nuclear translocation of NF‐κB, which can be modulated by G protein signaling pathway. These findings further suggest that inhibition of G protein‐mediated pathway by specific inhibitors may be a potential strategy for the prevention of arsenite toxicity. © 2015 Wiley Periodicals, Inc. Environ Toxicol 31: 1819–1833, 2016.